Fostering Talent Integration in Ontario’s Municipalities: Challenges and Best Practices - Harris, Neil; Lee , Nicola; Maksymenko, Tania; F.G. Moore , Nicole (Economic Development Journal of Canada, 2025)
In recent years, Ontario has experienced population growth due to an influx of new residents, including many newcomers to Canada. However, successful talent integration requires a win-win approach for both newcomers and the host community. To achieve this, stakeholders–including newcomer adults–must collaborate and define specific goals and outcomes for talent integration in urban, suburban, and rural communities. Communities must also understand the challenges and opportunities of talent integration and identify effective solutions that have worked in the past, such as employer-led initiatives, community-based transportation solutions, and culturally responsive services. By implementing best practices and prioritizing factors such as affordable housing, and cultural and linguistic integration, communities can promote the economic and social integration of newcomers while creating a more inclusive and diverse community that benefits everyone.